Personalised medicine for multiple sclerosis care. - Gafson,A; Craner,MJ; Matthews,PM (Multiple Sclerosis Journal, 2017)
Treatments with a range of efficacy and risk of adverse events have become available for the management of multiple sclerosis (MS). However, now the heterogeneity of clinical expression and responses to treatment pose major challenges to improving patient care. Selecting and managing the drug best balancing benefit and risk demands a new focus on the individual patient. Personalised medicine for MS is based on improving the precision of diagnosis for each patient in order to capture prognosis and provide an evidence-based framework for predicting treatment response and personalising patient monitoring. It involves development of predictive models involving the integration of clinical and biological data with an understanding of the impact of disease on the lives of individual patients. Here, we provide a brief, selective review of challenges to personalisation of the management of MS and suggest an agenda for stakeholder engagement and research to address them.